Pelatihan Penulisan Artikel Jurnal bagi Mahasiswa Program Studi Sastra Inggris Universitas Trunojoyo Madura - Pujiati, Tri; Alfisuma, Meria Zakiyah (Keris: Journal of Community Engagement, 2023)
Writing articles of a scientific nature is sometimes still an obstacle for final year English Literature students at Trunojoyo Madura University who want to publish the results of their research. This service activity is carried out by providing training on how to write scientific articles so that students are ready for publication. The method used is an approach based on Asset Based Community-Driven Development (ABCD). This activity is carried out through zoom meeting media during student holidays so that this activity is expected to fill student holiday time. The activity was carried out on July 26 2022. The results of this activity show that students have an interest in writing scientific articles but are still confused about starting and are still afraid to write. It is hoped that from this training students will become more confident and interested in writing scientific articles well and correctly